The problem of the commons: still unsettled after 100 years - Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2010)
The problem of the commons is more important to our lives and thus more central to economics than a century ago when Katharine Coman led off the first issue of the American Economic Review. As the U.S. and other economies have grown, the carrying-capacity of the planet - in regard to natural resources and environmental quality - has become a greater concern, particularly for common-property and open-access resources. The focus of this article is on some important, unsettled problems of the commons. Within the realm of natural resources, there are special challenges associated with renewable resources, which are frequently characterized by open access. An important example is the degradation of open-access fisheries. Critical commons problems are also associated with environmental quality. A key contribution of economics has been the development of market-based approaches to environmental protection. These instruments are key to addressing the ultimate commons problem of the twenty-first century - global climate change.
Keywords: Q22; Q28; Q50; Q54; Q58; 330; Common-Property Resource; Open-Access Resource; Fisheries; Global Climate Change